2005
DOI: 10.1111/j.0022-202x.2004.23562.x
|View full text |Cite
|
Sign up to set email alerts
|

Non-Invasive Visualization of Melanin and Melanocytes by Reflectance-Mode Confocal Microscopy

Abstract: In vivo visualization of epidermal melanin was performed by reflectance-mode confocal microscopy (RCM). Firstly, we examined the distribution of epidermal melanin in pigmented animals and compared with that of the human skin. Melanocytes in the skin of pigmented animals were found to accumulate a large amount of melanin that can be easily visualized because of its brightness. Their RCM images correlated well with the Fontana-Masson-stained sections for melanin. In contrast, in the human skin, typical dendritic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
65
0
4

Year Published

2005
2005
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(71 citation statements)
references
References 22 publications
2
65
0
4
Order By: Relevance
“…It has been reported that in type III (French) skin nuclear melanin caps were absent from basal keratinocytes in subjects tanned during their vacation period [23]. This has recently also been demonstrated in Japanese subjects [24]. This would indicate that the initial stages of the tanning process come from a redistribution of already preformed melanin and/or transfer of already synthesized melanosomes to suprabasal keratinocytes.…”
Section: Differences In Skin Colorationmentioning
confidence: 75%
“…It has been reported that in type III (French) skin nuclear melanin caps were absent from basal keratinocytes in subjects tanned during their vacation period [23]. This has recently also been demonstrated in Japanese subjects [24]. This would indicate that the initial stages of the tanning process come from a redistribution of already preformed melanin and/or transfer of already synthesized melanosomes to suprabasal keratinocytes.…”
Section: Differences In Skin Colorationmentioning
confidence: 75%
“…These melanosome accumulations (melanosome clusters or packaged melanosomes) form cap-like structures over the nuclei of keratinocytes to protect the nuclei from the damaging effects of ultraviolet radiation. The highest density of melanin is present in the epidermal basal layer as supranuclear melanin caps [3]. …”
Section: Discussionmentioning
confidence: 99%
“…The appearance of normal skin on RCM has been described to a limited extent. 1,15,16 Part of this work has been done using direct correlation with histology using horizontal tissue sectioning. 1 Without doubt, the intraindividual variation in RCM attributes of normal skin for different body sites (eg, trunk vs extremity), as well as the interindividual , compatible with pigmented basal keratinocytes, are aggregated almost back-to-back, in a cobblestone pattern.…”
Section: Discussionmentioning
confidence: 99%